The Impact of Urbanization and Demographic Shifts on Thailand's Economic Development - Khan, Aamer Shah; Kongjan, Nantasenamat; Farid, Shereen; Qureshi, Taza Khalid (International Journal of Humanities, Management and Social Science (IJ-HuMaSS), 2024)
This study examines the impact of urbanization and demographic shifts on economic development in Thailand, focusing on how these social changes affect key sectors such as tourism, manufacturing, and agriculture. The study aims to provide a comprehensive understanding of the economic implications of urbanization and aging population dynamics on the Thai economy, particularly through 2022. Using a mixed methods approach, the study combines quantitative data from surveys and statistical analysis, as well as qualitative data from stakeholder interviews. Quantitative analysis using regression models highlights the positive impact of urbanization on economic growth in urban centers, with significant contributions from the services, manufacturing, and tourism sectors. However, rural areas face slower economic growth due to labor migration. Demographic shifts, particularly an aging population, are associated with reduced labor availability, particularly in manufacturing and agriculture, leading to labor shortages and lower productivity. These findings emphasize the importance of addressing the urban-rural gap and adapting policies to an aging population. Key policy recommendations include balancing urban and rural development, optimizing labor force participation of older individuals, and investing in healthcare infrastructure. Limitations of this study include its focus on a specific region and sector, and future research could expand the scope of the impact of social change on other industries, explore longer-term effects, and integrate broader geographic data.